2002
DOI: 10.1159/000067895
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Sensing and Modulating Signals Arising From Cell Swelling

Abstract: Cell volume alterations are involved in numerous cellular events like epithelial transport, metabolic processes, hormone secretion, cell migration, proliferation and apoptosis. Above all it is a need for every cell to counteract osmotic cell swelling in order to avoid cell damage. The defence against excess cell swelling is accomplished by a reduction of the intracellular osmolarity by release of organic- or inorganic osmolytes from the cell or by synthesis of osmotically less active macromolecules from their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
100
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 296 publications
(289 reference statements)
5
100
0
Order By: Relevance
“…We conclude that PIP3 is more directly linked to the activation of VRAC current their effects on PIP3-regulated transporters and channels (4,8), further studies are necessary to clarify to what extent PI3K activation can increase the PIP3 level in intact cardiac cells. As with the relationship between cell swelling and PI3K-related signaling pathways, several reports have shown that mechanical stretch of membrane and cell swelling cause activation of PI3K (16), and the activated PI3K has been suggested to trigger some downstream signaling cascades leading to the activation of VRAC current (5,7,26,33). For example, Baumgarten and his colleagues (5) showed that ROS production by NADPH oxidase (NOX), which is formed by PI3K-dependent NOX subunits (p47 phox , p67 phox , Rac), was essential for activation of VRAC current in rabbit ventricular cells.…”
Section: Resultsmentioning
confidence: 99%
“…We conclude that PIP3 is more directly linked to the activation of VRAC current their effects on PIP3-regulated transporters and channels (4,8), further studies are necessary to clarify to what extent PI3K activation can increase the PIP3 level in intact cardiac cells. As with the relationship between cell swelling and PI3K-related signaling pathways, several reports have shown that mechanical stretch of membrane and cell swelling cause activation of PI3K (16), and the activated PI3K has been suggested to trigger some downstream signaling cascades leading to the activation of VRAC current (5,7,26,33). For example, Baumgarten and his colleagues (5) showed that ROS production by NADPH oxidase (NOX), which is formed by PI3K-dependent NOX subunits (p47 phox , p67 phox , Rac), was essential for activation of VRAC current in rabbit ventricular cells.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of cells to regulate their volume is essential for maintenance of cellular homeostasis under anisotonic environmental conditions (1)(2)(3). Changes in osmolarity of the extracellular medium induce water fluxes that result in swelling or shrinkage of cells, depending on the osmotic gradient.…”
mentioning
confidence: 99%
“…Most cells respond to changes in tonicity and cell volume by initiating mechanisms that allow them to recover their original volume in the continued presence of the osmotic stress. Such regulatory volume changes depend on the activation of cation and anion permeabilties that reverse the osmotic gradient and direction of water flow (1)(2)(3)(4). Emerging studies demonstrate that regulatory volume changes are critical for cell survival and also for regulation of cellular processes such as gene transcription and proliferation (1).…”
mentioning
confidence: 99%
“…Interestingly, these channels are also permeable to cations, organic osmolytes, and possibly ATP. Therefore, the (an)ion channels and the respective currents that are activated by cell swelling have recently been termed and are here referred to as regulatory volume decrease channels/currents (RVDC) (3,4).…”
mentioning
confidence: 99%
“…It is however still a matter of debate, as to whether the protein itself is a part of the molecular RVDC complex or rather acts as a regulator thereof (4,14), e.g. by interacting with integral membrane proteins or membrane-associated molecules.…”
mentioning
confidence: 99%